CXCL11 Correlates with Immune Infiltration and Impacts Patient Immunotherapy Efficacy: A Pan-Cancer Analysis - Li, Yang; Han, Shukun; Wu, Baokang; Zhong, Chongli; Shi, Yu; Lv, Chao; Fu, Lei; Zhang, Yizhou; Lang, Qi; Liang, Zhiyun; Yu, Yang; Tian, Yu (Frontiers in Immunology, 2022)
Background: Immunotherapy has achieved great success in cancer. Nevertheless, many patients cannot benefit from immune checkpoint blockade therapy because of the scantiness of CD8+ T cell infiltration in the tumor microenvironment (TME). CXCL11 is known as a regulator that influences T-cell infiltration into tumors. However, the role of CXCL11 in pan-cancer is still unclear. Methods: In this study, we investigated the expression and function of CXCL11 across 33 types of cancers based on datasets from The Cancer Genome Atlas (TCGA) database and the Genotype-Tissue Expression (GTEx) database. We analyzed the CXCL11 differential expression in tumor tissue and nontumoral tissue and in different stages of cancers. Moreover, the correlations among CXCL11 expression, prognosis, mismatch repair, tumor mutation burden (TMB), microsatellite instability (MSI), tumor microenvironment, and immune-related genes were evaluated. Results: CXCL11 expression was significantly higher in tumoral tissue than in nontumoral tissue for most types of cancer. Improved CXCL11 expression was related to an inconsistent prognosis in different cancers. CXCL11 was positively associated with CD8+ T cells and T follicular helper cells in the TME. High expression of CXCL11 was positively related to TMB in BLCA, BRCA, CESC, COAD, LGG, LUAD, OV, SKCM, STAD, THYM, and UCEC. A positive correlation between CXCL11 and MSI was found in COAD and UVM. Moreover, functional analysis of CXCL11 showed that high CXCL11 expression was significantly related to immune-relevant pathways. Conclusions: CXCL11 might function as a prognostic and immunotherapy marker across cancers. Further investigation into CXCL11 might provide promising insights to improve cancer therapy.